Women and Entrepreneurship – Albanian Case - Xheka, Anna (European Journal of Multidisciplinary Studies, 2016)
Women’s entrepreneurship is a powerful source, regarding to the women’s economic independence and empowerment, as well as regarding employment generation, economic growth and innovation, development and the reduction of poverty as well as one of the terms of gender equality. This poster presents the situation of women’s entrepreneurship in Europe in comparative terms, with special focus in Albania. The paper has a descriptive nature. Describes three different plans in comparative terms; the representation of men and women in entrepreneurship, the representation of women in entrepreneurship in different countries of Europe and of Europe as a whole, as well as compare to gender quota. Through the processing of secondary data from various reports and studies, this poster concludes that although that the gender equality goal is the equal participation of men and women in all sectors, including the entrepreneurship, in this sector, gender gap it is still deep. Another significant comparative aspect, it is the difference between full and part –time women entrepreneurship. While in full time entrepreneurship in a convince way, men are those that dominate, in part time entrepreneurship clearly it’s evident the opposite trend, women’s representation is much higher. It’s very interesting the fact, that the women’s entrepreneurship in Albania, presented in a significant optimistic situation, ranking in the second place, after Greece in the European level